2007
DOI: 10.1124/mol.107.039875
|View full text |Cite
|
Sign up to set email alerts
|

[3H]Org 43553, the First Low-Molecular-Weight Agonistic and Allosteric Radioligand for the Human Luteinizing Hormone Receptor

Abstract: The luteinizing hormone (LH) receptor plays a pivotal role in reproduction. The high-molecular-weight (HMW) human chorionic gonadotropin (hCG) and LH are the endogenous ligands of this receptor and bind to its large N terminus. The present study characterizes the binding of a new low-molecular-weight (LMW) radioligand, [ All displaced the radioligand competitively, with K i values ranging from 3.3 to 100 nM. Finally, the potency of these compounds in a cAMP-induced luciferase assay was also determined. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 28 publications
2
44
1
4
Order By: Relevance
“…109,110 Recently, a few other thienopyrimidines were reported by Heitman and coworkers. 111 The most potent compound (56; EC 50 ¼ 1.7 nM) was labeled with tritium and characterized for its receptor binding. It was shown that there was a high correlation between the affinity and potency of low molecular weight LH receptor agonists.…”
Section: A Thieno[23-b]pyri(mi)dine Derivativesmentioning
confidence: 99%
“…109,110 Recently, a few other thienopyrimidines were reported by Heitman and coworkers. 111 The most potent compound (56; EC 50 ¼ 1.7 nM) was labeled with tritium and characterized for its receptor binding. It was shown that there was a high correlation between the affinity and potency of low molecular weight LH receptor agonists.…”
Section: A Thieno[23-b]pyri(mi)dine Derivativesmentioning
confidence: 99%
“…Путем его модификации был получен более ак-тивный аналог Org 43553, который до сих пор счита-ют «золотым стандартом» низкомолекулярных аго-нистов ЛГР [9,10]. Соединение Org 43553 с высокой аффинностью (K d , 2,4 нМ) связывалось с ЛГР; свя-зывание было специфичным и не выявлялось в от-ношении рецепторов ФСГ и ТТГ.…”
Section: активность тиенопиримидиновых производных In Vitrounclassified
“…Сайты связыва-ния ЛГ и ТП с ЛГР не перекрываются, на что ука-зывают следующие факты. Во-первых, меченый радиоактивным йодом ХГЧ не вытесняет связан-ное с ЛГР соединение Org 43553, и, во-вторых, в присутствии ТП стимулирующий эффект ЛГ на АЦ сохраняется [9,11].…”
Section: активность тиенопиримидиновых производных In Vitrounclassified
“…2), которые относятся к тиенопиримидинам и активируют рецептор ЛГ со значениями EC 50 20 и 1,7 нМ соответственно [20,21]. Так Org43553 активирует рецептор ЛГ с эффективностью, составляющей 80% от таковой самого ЛГ, причем его действие является селективным -Org43553 в 10 раз слабее связывается с рецептором ФСГ и в 1000 раз слабее с рецептором ТТГ.…”
unclassified
“…Сходный результат достигается заменами некоторых аминокислотных остатков (АКО) в ТМ рецептора ЛГ, которые аллостерически модулируют связывание гонадотропинов с эктодоменом [23]. В-третьих, Org43553 также не по конкурентному механизму снижает вызываемую ЛГ стимуляцию активности фосфолипазы С (ФЛС) [21]. В-четвёртых, в присутствии ЛГ на 32% снижается связывание [ 3 H]Org43553 с рецептором ЛГ, что указывает на аллостерическую модель взаимного влияния эктодомена и серпантинного домена.…”
unclassified